PETROGRAPHIE DU GISEMENT D’OR DE BONIKRO, SILLON BIRIMIEN D’OUME - FETTEKRO, COTE D’IVOIRE - Zié Ouattara; Yacouba Coulibaly; François Lieben (European Scientific Journal, ESJ, 2015)
The Bonikro gold deposit is located in the southern part of the Oumé- Fettèkro birimian furrow. Its lithology is made of two primary rocks units; a mafic volcanic sequence in the East and a unit of volcano-sedimentary rocks in the western part. The interface of these two units is occupied by the Bonikro Shear Zone and the granodiorit. This intrusive is associated with the dykes of pegmatite and aplite, but also with volcanic giving the group of felsic rocks in the deposit. The minerals of sericite, chlorite, epidote observed in these rocks are consistent with the impacts of the greenschist facies metamorphism. Also, these lithologies are affected by a strong hydrothermal alteration due to the abundant veins of quartz, carbonate, albite, sulphide, scheelite and gold. The distribution of these aforenamed two units in the east and in the west supports the fact that the birimian has inherited the ancient valley. The various volcanic rocks are linked to the birimian volcanism, when the pyroclastites imply that this volcanism has undergone a possible period of explosive character.